Identification and characterization of the BmCyclin L1-BmCDK11A/B complex in relation to cell cycle regulation. Issue 9 (3rd May 2017) - Liu, Tai-hang; Wu, Yun-fei; Dong, Xiao-long; Pan, Cai-xia; Du, Guo-yu; Yang, Ji-gui; Wang, Wei; Bao, Xi-yan; Chen, Peng; Pan, Min-hui; Lu, Cheng
ABSTRACT: Cyclin proteins are the key regulatory and activity partner of cyclin-dependent kinases (CDKs), which play pivotal regulatory roles in cell cycle progression. In the present study, we identified a Cyclin L1 and 2 CDK11 2 CDK11 splice variants, CDK11A and CDK11B, from silkworm, Bombyx mori . We determined that both Cyclin L1 and CDK11A/B are nuclear proteins, and further investigations were conducted to elucidate their spatiofunctional features. Cyclin L1 forms a complex with CDK11A/B and were co-localized to the nucleus. Moreover, the dimerization of CDK11A and CDK11B and the effects of Cyclin L1 and CDK11A/B on cell cycle regulation were also investigated. Using overexpression or RNA interference experiments, we demonstrated that the abnormal expression of Cyclin L1 and CDK11A/B leads to cell cycle arrest and cell proliferation suppression. Together, these findings indicate that CDK11A/B interacts with Cyclin L1 to regulate the cell cycle.